Histopathological changes and Hirschsprung’s associated enterocolitis (HAEC) scores - Reinaldo Sunggiardi; Nita Mariana; Farid Nurmantu; . Ahmadwirawan; Tommy R. Habar; . Sulmiati; Harsali F. Lampus; Andi Alfian Zainuddin; . Prihantono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Histopathological changes that are usually permanent in the bowel of Hirschsprung’s disease (HRSC) in children make susceptibility to the incidence of enterocolitis even after definitive therapy. The pathophysiology of HRSC is characterized by specific signs, and symptoms. Scoring system has been applied in diagnosis of Hirschsprung’s associated enterocolitis (HAEC) due to its simplest and easiest. However, after a decade it has been several evaluated to obtain optimal benefits in the clinical setting. The aim of this study was to investigate the relationship between histopathological grade of enterocolitis and HAEC scores. Children with HRSC who underwent leveling colostomy or pull-through were sampled from the ganglionic segment. Those with a histopathological description of HAEC were included in the study. HAEC scores were evaluated retrospectively through medical records and interviews. Data were analyzed using the Spearman’s Rank test. Twenty eight samples were involved in this study. The population was dominated by male (82.1%) and almost half the population (42.9%) were infants. The distribution of the histopathological grade was fairly even, except for grade V where it was only 7.2% of the total sample. Grade I & III samples were 21.4%, while grade II & IV were 25%, respectively. A significant relationship between histopathological grade and HAEC score was obtained (r = 0.927; p<0.0001). In conclusion, there is a relationship between the histopathological grade of enterocolitis and HAEC scores.